A study of receptivity and technology transfer in small engineering companies. - Anstey, Mike (Cranfield University, 1993)
This thesis addresses the problem of facilitating technology transfer to SMEs (Small and Medium Enterprises). The research sets out to explore the existing body of knowledge relating to the problem, and then by means of field research to seek pointers towards solutions. The thesis builds on earlier research which identified weaknesses in the activities of information centred technology transfer intermediaries and called for a more interactive and consumer centred approach. The research is particularly concerned with the concept of the ’Receptivity’ of SMEs to the technology transfer process. The concept of ’Receptivity’ is examined in the context of a wider conceptual framework. The field research explores the problems and plans of a small sample of engineering companies in Luton as perceived by the owners or managing directors of the SMEs. The field research then seeks to establish how the same group perceive solutions to the identified problems and requirements to achieve identified plans. The research suggests that the SMEs in the sample did not perceive the acquisition of technology as a problem nor did they perceive technology as a solution to their problems, or as a means to achieve their plans. Conclusions are drawn and implications discussed.